Money Markets, Collateral, and Monetary Policy - De Fiore, Fiorella; Hoerova, Marie; Rogers, Ciaran; Uhlig, Harald (Review of Economic Studies, 2026)
We document dramatic changes in euro area interbank money markets during the financial and sovereign debt crises: unsecured borrowing declined across the euro area, while secured market haircuts on sovereign bonds increased, and bank borrowing from the European Central Bank rose in southern countries. We construct a quantitative general equilibrium model to assess the macroeconomic impact of these developments and the associated policy response. Our model features heterogeneous banks and sovereign bonds, secured and unsecured money markets, and a central bank. We compare a benchmark policy—the central bank providing collateralized lending to banks at haircuts lower than the market—with an alternative policy that maintains a constant central bank balance sheet. We show that the fall in output, investment, and capital would have been twice as high under the alternative policy.